Women and access to justice: a philosophical essay from the perspective of contemporary political liberalism - Caviglia Marconi, Alessandro (2013)
This paper explores the relationship between women and access to justice from the perspectiveof contemporary political liberalism of John Stuart Mill, Michael Walzr, John Rawls and MarthaNussbaum and Nancy Fraser post-socialist perspective.In this sense, it is distanced so much from the approach of the so-called third wave of feminism,because it rejects its centrality in the identity and in biology-based difference, as it also takes awayfrom the classic liberal approach defining the terms of justice regardless the voices of the subjectsinvolved.